Pengukuran Beban Kerja Mental pada Divisi QA/QC dan PPIC Menggunakan Metode NASA-TLX di PT Ciptaunggul Karya Abadi - Devinta Nurul Annisa; Rizki Achmad Darajatun (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2022)
PT Ciptaunggul Karya Abadi (CKA) is a company engaged in the manufacturing sector. PT Ciptaunggul Karya Abadi consists of several divisions, one of which is the QA/QC and PPIC Division. Every industrial company certainly produces an item that will later be traded. One of the things that plays a very important role in obtaining good production results is the workload factor for employees. Therefore, measuring the mental workload of employees is needed so that the production process in the company can be carried out properly and employees can work optimally. The purpose of this study was to measure and analyze the mental workload of employees in the QA/QC and PPIC divisions using the NASA-TLX method. Several stages in measuring mental workload use methods, namely weighting, rating, calculating the average WWL, and classifying workload assessments. The results of data processing show that the highest WWL average value is 83.33 in the very high category. To improve the mental workload, companies are advised to add workers to the QA/QC and PPIC Divisions as needed.